Structural Insight Into Chitin Degradation and Thermostability of a Novel Endochitinase From the Glycoside Hydrolase Family 18 - Wang, Yan-Jun; Jiang, Wen-Xin; Zhang, Yi-Shuo; Cao, Hai-Yan; Zhang, Yi; Chen, Xiu-Lan; Li, Chun-Yang; Wang, Peng; Zhang, Yu-Zhong; Song, Xiao-Yan; Li, Ping-Yi (Frontiers in Microbiology, 2019)
Bacterial endochitinases play important roles in environmental chitin degradation and have good applications. Although the structures of some endochitinases, most belonging to the glycoside hydrolase (GH) family 18 and thermostable, have been reported, the structural basis of these enzymes for chitin degradation still remain unclear due to the lack of functional confirmation, and the molecular mechanism for their thermostability is also unknown. Here, we characterized a GH18 endochitinase, Chi23, from marine bacterium Pseudoalteromonas aurantia DSM6057, and solved its structure. Chi23 is a thermostable enzyme that can non-processively hydrolyze crystalline and colloidal chitin. Chi23 contains only a catalytic domain that adopts a classical (β/α)8 TIM-barrel fold. Compared to other GH18 bacterial endochitinases, Chi23 lacks the chitin-binding domain and the β-hairpin subdomain, indicating that Chi23 has a novel structure. Based on structural analysis of Chi23 docked with (GlcNAc)5 and mutational analysis, the key catalytic residue (Glu117) and seven substrate-binding residues (Asn9, Gln157, Tyr189, Asn190, Asp229, Trp260 and Gln261) are revealed. Among these identified residues, Asn9, Asp229 and Gln261 are unique to Chi23, and their cumulative roles contribute to the activity of Chi23 against both crystalline and soluble chitin. Five substrate-binding residues (Tyr189, Asn190, Asp229, Trp260 and Gln261) are found to play important roles in maintaining the thermostability of Chi23. In particular, hydrogen bond networks involving Asp229 and Gln261 are formed to stabilize the protein structure of Chi23. Phylogenetic analysis indicated that Chi23 and its homologs represent a new group of GH18 endochitinases, which are widely distributed in bacteria. This study sheds light on the molecular mechanism of a GH18 endochitinase for chitin degradation.